Student Innovation in Campus Teaching: A Program to Improve Elementary School Student Literacy - Halimah, Halimah; Ningsih, Dinni Nurfajrin; Rahmawati, Siti Sukma; Patimah, Eva; Aulia, Fretty Puteri (Universitas Negeri Padang, 2024)
This study aimed to evaluate the impact of the Campus Teaching Student Innovation Program on improving the literacy skills of elementary school students. This study utilizes a Quantitative Research Method with a Pretest-Posttest Design to evaluate the effectiveness of the BeCa (Belajar Baca) and PoCi (Pohon Cita-Cita) program in improving literacy skills at Cikaratok Elementary School, Cianjur. Conducted in a fifth-grade classroom setting, the research involved a total of 28 students as participants. A pretest-posttest design was employed to measure the effectiveness of the program, with data analyzed using a gain index to assess progress. The findings indicated a moderate improvement in literacy skills, with an average gain index of 0.42, demonstrating the positive effects of the intervention. However, individual variations in progress highlighted the need for more personalized and targeted teaching strategies. This research underscores the importance of creative and innovative approaches in literacy education to address diverse student needs and foster meaningful learning outcomes.